Human Motion Estimation Application for the Marker-Based Motion Capture Systems - Lukic, Branko; Radmilovic, Marija; Becanovic, Filip (2024 11th International Conference on Electrical, Electronic and Computing Engineering (IcETRAN), 2024)
Motion capture technology finds wide application in various fields such as entertainment, sports analysis, and biomechanics, enabling accurate digitization of real-world movements for replication in digital environments. There exist diverse motion capture systems utilizing different technologies, supported by software tools for marker movement extraction. Further processing of acquired data requires additional investment in software development. This paper presents the human motion estimator application developed using GUI in MATLAB App Designer. This application aims to generate human movement based on recorded marker data obtained from motion capture systems (MCS), currently supporting two MCSs: Vicon and ART. The developed application aims to become a universal tool for estimating human movements, supporting data from ART or Vicon MCS. The application provides visual instructions for mounting markers on the body and initialization position, while data processing is based on optimization algorithms for defined criteria functions. The application targets research institutions by providing essential software support for ART or Vicon MCSs, thus enhancing data analysis capabilities for estimating upper body movement. The application is a framework, a starting point, to be upgraded and future developed with additional MCS and features.